Diffusion-Weighted Imaging, MR Angiography, and Baseline Data in a Systematic Multicenter Analysis of 3,301 MRI Scans of Ischemic Stroke Patients—Neuroradiological Review Within the MRI-GENIE Study - Drake, Mattias; Frid, Petrea; Hansen, Björn M.; Wu, Ona; Giese, Anne-Katrin; Schirmer, Markus D.; Donahue, Kathleen; Cloonan, Lisa; Irie, Robert E.; Bouts, Mark J. R. J.; McIntosh, Elissa C.; Mocking, Steven J. T.; et al. (Frontiers in Neurology, 2020)
Background Magnetic resonance imaging (MRI) serves as a cornerstone in defining stroke phenotype and etiological subtype through examination of ischemic stroke lesion appearance and is therefore an essential tool in linking genetic traits and stroke. Building on baseline MRI examinations from the centralized and structured radiological assessments of ischemic stroke patients in the Stroke Genetics Network (SiGN), the results of the MRI-Genetics Interface Exploration (MRI-GENIE) study are described in this work. Methods The MRI-GENIE study included patients with symptoms caused by ischemic stroke (n=3300) from 12 international centers. We established and used a structured reporting protocol for all assessments. Two neuroradiologists, using a blinded evaluation protocol, independently reviewed the baseline diffusion-weighted images (DWI) and Magnetic Resonance Angiography (MRA) images to determine acute lesion and vascular occlusion characteristics. Results In this systematic multi-center radiological analysis of clinical MRI from 3300 acute ischemic stroke patients according to a structured prespecified protocol, we identified that anterior circulation infarcts were most prevalent (67.4%), that infarcts in the MCA territory were the most common, and that the majority of large artery occlusions 0-48 hours from ictus were in the MCA territory. Multiple acute lesions in one or several vascular territories were common (11%). Of 2238 patients with unilateral DWI lesions, 52.6% had left-sided infarct lateralization (P = 0.013 for χ² test). Conclusions This large-scale analysis of a multicenter MRI-based cohort of AIS patients presents a unique imaging framework facilitating the relationship between imaging and genetics for advancing the knowledge of genetic traits linked to ischemic stroke.